First luminescence chronology of late Holocene deposits of the tropical Atrato Delta, Colombia. (December 2020) - Betancurth, Liliana; Preusser, Frank; Mueller, Daniela; Rambeau, Claire; Cañón, Julio
Abstract: Sediments of the Atrato River Delta, Colombia, were investigated to determine the late Holocene dynamics by using luminescence dating. For this introductory study, near-surface samples were collected along the main river channel and around the main delta body, while sediment cores were drilled at three swamps and in two bays. Altogether, 30 samples were collected to determine ages and accumulation rates in both marine and inland settings. The samples proved to be a methodological challenge, but the dating results and derived sediment accumulation rates are conclusive. Homogenous accumulation rates of less than 2 mm a −1 have been found for most settings of the delta, despite differences expected from the sedimentary facies. These accumulation rates are similar in magnitude to those reported for other tropical deltas. Interestingly, a significant increase in accumulation rates is observed in parts of the Atrato Delta that might be related to human activity during the early colonization by Europeans. The contribution of new data and sedimentary information derived from this study may serve as a baseline for future sampling campaigns aiming at gaining more comprehensive insights into the sedimentary dynamics of the Atrato Delta. Highlights: Late Holocene sediments of the Atrato River Delta dated by IRSL. Accumulation rates of less than 2 mm a −1 found for most settings of the delta. Accumulation rates are similar in magnitude to those of other tropical deltas. Higher accumulation rates likely related to human activity during early colonization by Europeans.